Use and Abuse of Trafficking Discourse in Japan - Ogawa, Reiko (Journal of Population and Social Studies [JPSS], 2020)
Global human rights norms function as resources for state and civil society by facilitating or hindering mobility, ensuring the protection of migrants, promoting equal treatment, and providing remedies for human rights violations. While these global norms have inspired numerous actors and set standards, the internalization of such global norms is left to national political mechanisms. This paper examines the translation and appropriation of trafficking discourse in Japan and discusses its implications. The research questions addressed are as follows: (1) How has the trafficking discourse been translated and appropriated in Japan? (2) What are the policy implications concerning trafficking discourse? and (3) What has been concealed by this appropriation of trafficking discourse? The research utilized government documents, particularly police and immigration reports, as well as annual reports on trafficking. These documentary sources were supplemented by interviews with police and immigration officers, migrants, and civil society actors. The formation of a trafficking discourse represents a shift from perceiving migrant women as ‘criminals’ to seeing them as ‘victims of trafficking.’ Since the associated domestic institutions are embedded within abolitionist and criminal justice approaches, the agency of migrants has not been considered. The trafficking discourse legitimizes border control and securitization under the name ‘prevention’ while concealing other forms of exploitation conducted via legal labor migration channels. Trafficking must be situated within the labor migration continuum, and a safe, orderly migration corridor must be established. This stance, along with ensuring labor rights for both Japanese and migrants—particularly among women—is the best track to approach the issue of human trafficking.